Profile of p53 Protein Expression in Basal Cell Carcinoma Low-Risk and High-Risk Subtype - Alendra Chakramurty; Meira Dewi Kusuma Astuti; Hermawan Istiadi; Awal Prasetyo; Dik Puspasari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Basal cell carcinoma is one of the most common cancers in the world, and its incidence is increasing over time. It is estimated that it accounts for three-quarters of all non-melanoma skin cancers, and the incidence increases exponentially in predominantly white areas. The p53 gene is the gene that most undergoes mutations due to sun exposure and is the cause of skin cancer, especially basal cell carcinoma. This finding explains that p53 expression can be used as marker analysis in cases of basal cell carcinoma. Methods: Observational analytic design was carried out with a cross-sectional. The population and samples were paraffin blocks which histopathologically diagnosed Basal Cell Carcinoma in the anatomical pathology laboratory, Dr. Kariadi General Hospital Semarang. Samples were processed by the p53 immunohistochemical staining method. The p53 expression was given a quantitative score to be 0 = negative, 1-2 = low, 3-4 = high. The expression of p53 was considered positive when it was colored in the cell nucleus. The correlation between variables was analyzed by Spearman and Mann Whitney correlation test. Results: There is no correlation between p53 expression and the age of p53 patients with p = 0.390 (p > 0.05). There is no correlation between p53 expression and lesion location with p = 0.817 (p > 0.05) There is no difference significant, between p53 expression and gender with p = 0.576 (p > 0.05). Conclusion: There is no correlation between high and low-risk Basal Cell Carcinoma subtype associated with age, gender, and lesion location.